Polar vortex dynamics on gas giants: Insights from 2D energy cascades - Jiaru Shi; Wanying Kang (Proceedings of the National Academy of Sciences, 2026)
The distinct polar vortex dynamics observed on Jupiter and Saturn may provide insights into their interiors. In this study, we examine how the number and structure of polar vortices vary with forcing strength, dissipation rate, and interior stratification using a 1.5-layer quasi-geostrophic model. This simplified setup enables a broad exploration of the parameter space, revealing that vortex characteristics are determined by the sequence in which three key length scales—the deformation radius L d , the zonostrophic scale L γ , and the dissipative scale L μ —are encountered as energy cascades from small to large scales. Four distinct vortex patterns are identified, including a vortex crystal resembling Jupiter’s polar vortices and a single-vortex state akin to that of Saturn. The conditions under which these patterns emerge provide constraints on the stratification of Jupiter and Saturn.